Pengaruh Flexible Work Arrangement terhadap Employee Engagement pada Pekerja Usia Dewasa Awal - Lubis, Irma Rosalinda; Ishak, Shaumi Annisa (Jurnal Online Psikogenesis, 2023)
The aim of this study is to investigate the influence of flexible working arrangement on employee engagement in early age workers. This research is  quantitative research. The subject of this study was 218 partcipants who were obtained using a convenience sampling technique. Methods of data collection was obtained with questionnaires both online and in person. Analysis statistical test that is used to examine the hypothesis is multiple linear regression. The result of this study indicates that there is a significant influence of flexible work arrangement on employee engagement in early age workers. The value of the coefficient of determination is 0,24. This means that flexible working arrangement affects employee engagement by 24%.